Consensus problems in multiagent systems: A vector based contraction approach - Singh B.; Xiong X.; Kamal S.; Ghosh D.; Ghosh S. (My University, 2025)
This paper addresses the exploitation of vector based contraction theory to synchronize the motion of agents in multiagent systems. The convergence analysis of the agents using this theory provides a flexible frame as the components of a vector distance norm follow less stringent conditions than classical contraction analysis. The key feature is that it encompasses the formulation of some comparison system, as a result, the problem of convergence analysis of a complex multiagent system reduces to the convergence analysis of a much simpler comparison system. Hence, despite the nonlinearities, the methods of designing consensus controls remain simple as compared to the existing literature. We address four different cases: 1) consensus of third-order dynamics multiagent systems subjected to acceleration and input constraints; 2) consensus of multiagent systems with heterogeneous nodes under communication imperfections; 3) synchronization of multiagent systems with connected and disconnected switching topologies; 4) synchronization in networked systems with time-varying couplings. Moreover, an effective synchronization control scheme for a class of multiagent systems with underactuated agent dynamics is developed using the method of aggregation of comparison systems. Finally, simulation results are illustrated that show the validity of the mathematical results. © 2021 The Authors. IET Control Theory & Applications published by John Wiley & Sons Ltd on behalf of The Institution of Engineering and Technology